Management Strategy in a Large Accounting Firm: A Reply. - Baker, C. Rickard (The Accounting Review, 1979)
Abstract The article presents a reply to a comment made by Kenneth Brooks and Richard Schroeder on an article by the author, "Management Strategy in a Large Accounting Firm." In regard to the comment that the time frame chosen was not appropriate, the author responds that the time frame chosen was probably the most appropriate of any that could have been chosen, in that it was a cross-section of all of the activities that the firm is engaged in and not merely auditing. The full range of activities was observed, including field auditing situations. Indeed, it was found that observing field auditing was not particularly helpful towards developing an understanding of management strategy, and that it was only in the office environment that such strategy was fully revealed. Although it was imperative that client confidentiality be maintained, there were no impediments placed in the way of observation by management of the firm. The author does not believe that he implied that all successful firms follow the same strategy which he observed. In fact, the paper specifically indicates that this was a model of a successful firm, not all successful firms.